Kiribati : 2015 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2015)
KEY ISSUES Context. Donor-financed large infrastructure projects, increased public spending, and a pick-up in credit to households have boosted real GDP growth to close to 4 percent in 2014 and to about 3 percent in 2015. Inflation remains low, underpinned by lower food and commodity prices. Steps are being taken to reduce the many hurdles to private growth that Kiribati faces, among which are high transportation and communication costs and an increasing impact of climate change. Fiscal policy. The fiscal outlook has improved, but further efforts are needed to ensure sustainability. The recurrent balance was in large surplus in 2014 and is expected to remain positive in 2015, reflecting high revenue from license fees, and notwithstanding a large increase in expenditures. But under the historic pace of spending the sovereign wealth fund (Revenue Equalization Reserve Fund-RERF) would be depleted in about 20 years. Ensuring sustainability requires containing nominal expenditure growth to around 1 1\2 per annum over the next five years (after accommodating climate-change-related costs), with transparent and symmetric transfers and withdrawals from the RERF around this path. Structural reforms. There is a consensus among donors that significant progress has been achieved. The State-Owned Enterprise (SOE) Reform Act is being implemented in a satisfactory way, as illustrated by the recent successful privatization of the telecommunication company. Key outstanding issues include further reforming the energy and copra sectors and improving the investment climate.